(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The Lamiaceae Martinov family has about 200 genera and 3500 species, distributed in all climatic zones, with the highest species diversity in the Mediterranean. There are 35 genera in Ukraine, 180 species (together with the most cultivated ones) and stabilized hybrid forms described in the species status. The most significant nomenclature changes occurred in the segregate genera Acinos Mill., Calamintha Mill., Clinopodium L., and Micromeria Benth., the species of which were included in the genus Clinopodium L. The polyphiletic genus Micromeria Benth. has undergone nomenclature changes and a significant part of its taxa is excluded from the genus (African species are included in the genus Saturea L.). A number of these species, among which Micromeria serpyllifolia (M.Bieb.) Boiss. represented in Ukraine, included in the genus Clinopodium L., as well as in some other related genera. The genus Majorana Mill. included in the Origanum L. genus. Species of the genus Phlomis L. considered within two genera: Phlomis and Phlomoides Moench, many of which, described from the territory of Ukraine, and treated as synonyms. The genus Rosmarinus L. (R. officinalis L.) is included in the genus Salvia L. For each species, its distribution in Ukraine indicated, and the notes provide data on their variability and taxonomic affiliation.